Prevalence Of Anemia and Nutritional Status Comparison in Urban and Rural Areas Among Underfive Children - Muchalambi, Vaishali (Journal of Neonatal Surgery, 2025)
Background: The prevalence of anemia stays high across various research studies which emerge from different regions. Anemia which results from low blood hemoglobin levels operates as a severe global public health matter. Public health initiatives need to identify cases of anaemia. Global data from 2011 indicates that anemic conditions affected 273 million young children worldwide particularly from iron deficiency triggers about 50% of that number. IDA functions as an important determinant for the deaths of mothers and newborns and increases their susceptibility to stillbirth and premature delivery along with low birth weight. The condition directly leads to premature deaths along with disability. The research examined the differences in urban-rural hemoglobin levels and anthropometric measurements together with child nutritional status and anemia frequency. About 25.8% of participants had mild anemia whereas moderate anemia affected 10.8% and severe anemia affected 3.3% among the study population. Mild anemia stands as the leading type of anemia which appears within the studied group. Public intervention programs need to recognize multiple anemia-related factors before studying interventions for reducing anemia prevalence. For anemia prevention strategies to be most effective they need integrated implementation at the targeted and coordinated system level. Successful reduction of child anemia requires cohesive efforts between local communities government organizations and non-government organizations as well as additional groups